2018
DOI: 10.1093/ptj/pzy084
|View full text |Cite
|
Sign up to set email alerts
|

Terminology of Pelvic Floor Muscle Function in Women With and Without Urinary Incontinence: A Systematic Review

Abstract: A large variation in PFMF terminology was identified, precluding data gathering and meta-analysis. The lack of use of standardized terminology delays the progress of scientific knowledge and evidence-based practice dissemination. Efforts toward creating a collaborative, consensual terminology based on a sound framework are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“… Number of contractions repeated within a specific duration (i.e., a 10‐s period 5 ) The elapsed time to perform a pre‐specified number of contractions (e.g., 10 s 69 ) …”
Section: Section 2: Signsmentioning
confidence: 99%
See 3 more Smart Citations
“… Number of contractions repeated within a specific duration (i.e., a 10‐s period 5 ) The elapsed time to perform a pre‐specified number of contractions (e.g., 10 s 69 ) …”
Section: Section 2: Signsmentioning
confidence: 99%
“…There is a plethora of existing terms and conceptual and operational definitions related to PFM function and dysfunction 5 . Saltiel et al 5 observed inconsistency and redundancy in PFM function terminology and suggested that a further consideration of PFM function terms relevant to research and to clinical practice is required 5 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…MVC of PFM can be considered a muscle characteristic associated with the continence mechanism, 40,41 since it seems to be associated with the presence of PFM dysfunctions. 42 The prevalence of PFM disorders was varied in the present study.…”
Section: Discussionmentioning
confidence: 99%